Does monetary policy have asymmetric effects? A look at the investment decisions of Italian firms - Eugenio Gaiotti; Andrea Generale (European Central Bank (ECB), 2001)
This paper studies the effects of monetary policy on the investment behaviour of various categories of Italian firms, using a panel from the Company Accounts Data Service (Centrale dei Bilanci). The exercise aims to shed light on the quantitative importance of a channel of transmission operating through balance sheets. Financial variables matter (when defined as either cash flow or the stock of liquidity); small firms and firms which have a larger share of assets that cannot be used as collateral are more affected by monetary policy. In quantitative terms, the difference in the response of investment by different types of firms turns out not to be negligible; however, the implications of this finding for transmission asymmetries across euro-area countries should not be overemphasized. Our main policy conclusion is that monitoring the financial conditions of different types of firms is important in order to assess the overall monetary stance
Keywords: E22; E50; 330; Investment; monetary transmission; user cost of capital